2021
DOI: 10.1021/acsenergylett.1c02076
|View full text |Cite
|
Sign up to set email alerts
|

Defect Spectroscopy in Halide Perovskites Is Dominated by Ionic Rather than Electronic Defects

Abstract: See https://pubs.acs.org/sharingguidelines for options on how to legitimately share published articles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 46 publications
4
26
0
Order By: Relevance
“…On mixed conductors as HPs, one must be cautious about whether the measured signals are due to ionic or electronic defects, otherwise mistaken conclusions may be drawn. [51] Identifying the type of mobile defect is not easy and a number of reports predict the facile migration of halide-related defects, under biasing conditions, rather than MA and Pb vacancies, with calculated activation barriers of %0.5 and 0.8 eV, respectively. [6,52] Correlations between specific ionic defects and electronic doping mechanisms have been made based on how the doping concentration is modified during the application and switching-off of an external bias.…”
Section: Resultsmentioning
confidence: 99%
“…On mixed conductors as HPs, one must be cautious about whether the measured signals are due to ionic or electronic defects, otherwise mistaken conclusions may be drawn. [51] Identifying the type of mobile defect is not easy and a number of reports predict the facile migration of halide-related defects, under biasing conditions, rather than MA and Pb vacancies, with calculated activation barriers of %0.5 and 0.8 eV, respectively. [6,52] Correlations between specific ionic defects and electronic doping mechanisms have been made based on how the doping concentration is modified during the application and switching-off of an external bias.…”
Section: Resultsmentioning
confidence: 99%
“…36−39 Interpretation of the low-frequency response has been attributed to the impedance of trap states, 12,40 an impedance due to degradation in the device, a giant dielectric effect, 41,42 an impedance due to electron accumulation at the contacts, 38,43 and ionic diffusion. 44,45 We observed two responses in the IS spectra of all measured devices, a low-frequency response γ (<10 2 Hz) at high temperatures (>315 K) and a high-frequency response (>10 2 Hz) β, present at all temperatures, 46 shown in Figure S1. In our previous work, based on emission rates obtained through conventional and reverse deep level transient spectroscopy, we found that these two defects are ionic in nature.…”
mentioning
confidence: 82%
“…The resistance has been attributed to an electron transport resistance, an ion transport resistance, or a recombination resistance. The capacitance has been connected to the geometric capacitance, chemical capacitance, or a capacitance due to dipole depolarization or ionic diffusion in the perovskite material. Interpretation of the low-frequency response has been attributed to the impedance of trap states, , an impedance due to degradation in the device, a giant dielectric effect, , an impedance due to electron accumulation at the contacts, , and ionic diffusion. , …”
mentioning
confidence: 99%
“…A pertinent question to ask, then, is, Are the methods used to estimate these defect densities, often as trap or (net) carrier densities, valid for HaPs? For one of these methods, space-charge-limited current, this issue has been studied in some detail, and variations have been proposed to take into account the possibility of ion migration during the measurement. , For measurements at low temperatures, such as some deep-level transient spectroscopy and thermally stimulated current ones, ion migration effects can be expected to be smaller than for RT measurements, but the above-discussed dynamic effects may strongly alter the quantitative analysis of the measured signals . The signature of low defect densities can also be detected by other means, notably surface photovoltage spectroscopy, as well as from careful analyses of standard, or low, variable energy ultraviolet photoemission spectroscopy experiments. , …”
Section: What Are Defect Tolerance and Self-healing?mentioning
confidence: 99%
“…62,63 For measurements at low temperatures, such as some deeplevel transient spectroscopy and thermally stimulated current ones, ion migration effects can be expected to be smaller than for RT measurements, but the above-discussed dynamic effects may strongly alter the quantitative analysis of the measured signals. 64 The signature of low defect densities can also be detected by other means, notably surface photovoltage spectroscopy, 65−67 as well as from careful analyses of standard, or low, variable energy ultraviolet photoemission spectroscopy experiments. 68,69 To summarize, for DT to hold, the defects that are present but tolerated must be mostly inactive, electrically and optically.…”
mentioning
confidence: 99%